2013
DOI: 10.5761/atcs.oa.12.02234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Health Related Quality of Life of Patients Following Mitral Valve Surgical Procedures in the 6-Months Follow-up: A Prospective Study

Abstract: Purpose: The aim of the present study is to evaluate the health-related quality of life of the patients who underwent mitral valve repair (MvRp) and mitral valve replacement (MVR). Methods: Within the scope of this prospective study design, 56 patients who had mitral valve operation between the years of 2011-2012 were enrolled in the study. 24 (42.8%) of these patients had MVR while 32 (57.1%) of them had MvRp. The health-related quality of life was evaluated according to the Turkey norms of Short Form 36 Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Comparing early HRQoL by study location and valve position, recipients of aortic valves in the UK 30 had significant improvement in seven of eight health domains ( p <0.05). In contrast, the mitral-valve recipients in the (UK 30 and Turkey 36 had significant improvement in only five of eight domains. The mitral-valve sample in the UK had no significant improvement in general or mental-health, whereas for the Turkish mitral-valve sample, the opposite was true.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Comparing early HRQoL by study location and valve position, recipients of aortic valves in the UK 30 had significant improvement in seven of eight health domains ( p <0.05). In contrast, the mitral-valve recipients in the (UK 30 and Turkey 36 had significant improvement in only five of eight domains. The mitral-valve sample in the UK had no significant improvement in general or mental-health, whereas for the Turkish mitral-valve sample, the opposite was true.…”
Section: Resultsmentioning
confidence: 81%
“…Three studies, all on isolated valve procedures, measured and compared preoperative HRQoL to early postoperative HRQoL. 30,31,36 Whilst all HRQoL domain mean-scores demonstrated positive change (Table 3), this reached statistical significance ( p < 0.05) consistently across all studies in four of the eight domains (physical-functioning, role-physical, vitality and social-functioning). Goldsmith et al 31 and Ay et al 36 also identified significant improvement in the domains of general-health and mental-health with the Goldsmith et al 30,31 studies additionally finding significant improvement in the role-emotional domain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Replacement or repair of the damaged valves, which accounts for 28.2% of all cardiac surgery in China (He, Zhu, Hou, Long, & Zhao, 2017), usually improves patients' heart function, relieves symptoms, and improves quality of life (QOL; Astin et al, 2017;Ay et al, 2013). However, replacement or repair of the damaged valves carries substantial risks, with a mortality rate from 3.1% to 4.5% postoperatively among patients with VHD (Han, Yu, Zhu, Huang, & Sun, 2017;Yan, Wang, Han, Lu, & Xu, 2013).…”
Section: Introductionmentioning
confidence: 99%